Autoimmune encephalopathy associated with thyroid autoantibodies as the cause of reversible cognitive impairment - Robert Dobbin Chow; Nechama Bernhardt; Natallia Maroz (Greater Baltimore Medical Center, 2012)
We herewith describe a patient with acute confusion, expressive aphasia and generalized seizures. A through workup excluded most causes of encephalopathy. He was, however, found to have TSH = 18.6 MIU/ml, T3reverse = 0.44nmol/L, T4 = 0.8ng/dl and Anti-Thyroid-Peroxidase AB titer >1000 IU/ml. Based on the above findings the patient was diagnosed with Hashimoto's encephalopathy and his mental status showed dramatic improvement (MMS 30/30) with high dose prednisone. Hashimoto's encephalopathy is rare disorder of presumed autoimmune origin characterized by cognitive decline, seizures, neuro-psychiatric symptoms, high titers of Anti-Thyroid-Peroxidase AB, and a positive response to steroids.